Monitoring System of Temperature and Body Weight for Baby Incubator Design Using BASCOM-AVR - Febrina, Dewi Cahya (Merdeka Malang University, 2024)
Baby incubator is a tool for maintaining the warmth of the baby after birth so they are able to adapt with external environment. The main feature of incubator is setup room temperature for maintaining baby’s temperature to avoid hypothermia. However, for premature babies it is not only strict temperature regulation, but also many procedures, such as monitoring their body weight regularly as the indicators to determine the development of baby’s health. Baby incubator with temperature and baby weight control system is needed to make it easier for paramedics to monitoring the baby’s progress while in the incubator. System design of incubator is designed with the room temperature controller ON-OFF system in the range of 30oC – 35oC and wight scale system in the range of 0 kg – 5 kg. Incubator box will be installed using blower 12VDC and heater driver. Temperature and weight controller system is designed using BASCOM-AVR software. This research is hoped that this simple incubator design can be applied to small-scale baby health centers, such as baby clinics and community health centers.